2022
DOI: 10.1186/s13058-022-01591-3
|View full text |Cite
|
Sign up to set email alerts
|

Mebendazole prevents distant organ metastases in part by decreasing ITGβ4 expression and cancer stemness

Abstract: Breast cancer is the most diagnosed cancer among women. Approximately 15–20% of all breast cancers are highly invasive triple-negative breast cancer (TNBC) and lack estrogen, progesterone, and ERBB2 receptors. TNBC is challenging to treat due to its aggressive nature with far fewer targeted therapies than other breast cancer subtypes. Current treatments for patients with TNBC consist of cytotoxic chemotherapies, surgery, radiation, and in some instances PARP inhibitors and immunotherapy. To advance current the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
(67 reference statements)
0
11
0
Order By: Relevance
“…Nair et al [7] have previously demonstrated that cytoskeletal drugs (such as tubulin binder MBZ) are more effective against cancers with high predicted migration capacity. Consistently, MBZ has been shown to slow down tumor growth and/or prevent metastatic spread of TNBC in animal models using multiple cell lines [14,38,39]. To our knowledge, no studies were comparing MBZ effect on tumor growth and/or survival for distinct breast cancer isotypes.…”
Section: Mbz Reduced the Migration Of Tnbc Cell Lines Mda-mb-231 And ...mentioning
confidence: 84%
See 2 more Smart Citations
“…Nair et al [7] have previously demonstrated that cytoskeletal drugs (such as tubulin binder MBZ) are more effective against cancers with high predicted migration capacity. Consistently, MBZ has been shown to slow down tumor growth and/or prevent metastatic spread of TNBC in animal models using multiple cell lines [14,38,39]. To our knowledge, no studies were comparing MBZ effect on tumor growth and/or survival for distinct breast cancer isotypes.…”
Section: Mbz Reduced the Migration Of Tnbc Cell Lines Mda-mb-231 And ...mentioning
confidence: 84%
“…MBZ was successfully tested in multiple preclinical tumor models, including glioma [11,13,45] and TNBC [14,38]. Several active and/or recruiting clinical trials investigating the anticancer effect of MBZ, alone or in combination with other drugs, are currently registered at clinicaltrials.gov [18,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancer (BC) is the most common tumor in women (Joe et al, 2022). Among them, triple-negative breast cancer (TNBC) is the most invasive subtype of BC, featured by the lack of estrogen and progesterone receptors, and the poor or lack of expression of human epidermal growth factor-2 (HER-2) (Sixto-Lopez, Ordaz-Pichardo, Gomez-Vidal, Rosales-Hernandez, & Correa-Basurto, 2023; .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has proven effective in reducing tumor growth and lung and liver metastasis. Furthermore, MBZ can diminish CSC characteristics, attributed to its ability to target the expression of β4 integrin [59]. Additionally, MBZ reduced the hypoxia response in BC cells and a mouse model of BC by targeting both HIF-1α-and HIF-1β-mediated transcription [60].…”
Section: Sensitization Of Bc Cells With Anthelmintic Drugsmentioning
confidence: 99%